(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
Like private television networks, RAI tries to differentiate and characterize its original TV programs, adopting particular creative lines. This essay aims to analyse the production logics of RAI Cultura, an organization created in 2014 from the ashes of RAI Educational, which produces pedagogical and informative content. The first part is dedicated to the analysis of telecasts, where educational programming and projects targeted at tweens are alternated with more in-depth themes for a general audience. The second part reflects on the evolution of these two strands in their transition to online platforms, and therefore rethinks the very concept of production.